An exploratory study of the use of social media to assess benefits realization in transport infrastructure projects - Sandeep Mathura; Johan Ninan; Lauri Vuorinen; Yongjian Ke; Shankar Sankaran (Project Leadership and Society (PLAS), 2021)
Infrastructure projects such as metro rails are being increasingly built in busy cities mainly to improve mobility and reduce congestion. However, assessment of benefits realized from these projects is complex. One reason for this is that promoters of these projects often misrepresent the projects' benefits to get them approved. Although some benefits from infrastructure projects can be measured using economic data, such data are insufficient for measuring social benefits. This article reports on an exploratory study on how social media could provide an opportunity to evaluate benefits qualitatively by analyzing tweets from metro rail projects in India and Australia. Although the analysis of tweets from these projects indicated that citizens who use these transport facilities report benefits, they do not seem to use the same terms as the project's promoters to describe these benefits. The article concludes with some suggestions on how social media can supplement current methods used in evaluating benefits from transport projects.
Keywords: 650; Transport infrastructure; Social media; Benefit evaluation; Project value; Benefits management